Influências de biofertilizantes nos teores foliares de macronutrientes, nas trocas gasosas, na produtividade e na pós-colheita da cultura do melão - Santos, Ana Paula Guimarães (2012)
The melon (Cucumis melo L.) is the eighth most widely produced fruit in the world, occupying the third position among the leading fresh fruit exported by Brazil. However, the melon has high expenditures on fertilizers and pesticides showing the possibility of using alternative products such as organic fertilizers and bio-fertilizers to reduce costs and environmental damage. In this context, the present study aimed to evaluate foliar nutrients (N, P, K, Ca, Mg and S), gas exchange, productivity and post-harvest melon crop farming Mirage Following Harper, subjected to different doses and types of biofertilizers. The experiment was conducted in the experimental area of the Meteorological Station of the Federal University of Ceará (UFC), in Fortaleza, Ceará. The experiment was randon blocks design in factorial arrangement 4 × 2 + (2), referring to 4 doses of biofertilizers (0.5, 1.0, 1.5 and 2.0 weeks L-1), 2 types of biofertilizers liquids (mixture of B1 = B2 = aerobic fermentation and biofertilizer simple anaerobic fermentation) with two additional treatments (control and chemical fertilizer). The variables analyzed were: foliar N, P, K, Ca, Mg and S, photosynthesis, transpiration, stomatal conductance, fruit yield, fruit weight, fruit diameter, brix, total acidity, firmness, flesh thickness and the pulp cavity. Biofertilizers mixed beef and can be used as a source of nutrients in growing melon cultivar Mirage Following Harper, however, no need for high dosages to meet the requirement of the crop. At higher doses, the simple biofertilizer led to the highest rate of photosynthesis, stomatal conductance and transpiration in relation to mixed biofertilizer. The dose of biofertilizer joint that maximizes the productivity (32.628 Mg ha-1) was estimated at 1.085 melon, L-1 plant week-1. The mixed biofertilizer led to higher average weight and diameter of fruits and productivity, most of the dosages used. The use of biofertilizer mixed enabled increased steadily, the pulp chamber and titratable acidity